Peningkatan Keterampilan Menulis Cerpen Menggunakan Model Pembelajaran Round Table di Sekolah Dasar - Mulya; Marta, Rusdial; Fadhilaturrahmi, Fadhilaturrahmi; Citra , Mulya (Universitas Nusantara PGRI Kediri, 2023)
Through the use of the round table learning method, this study seeks to improve the short story writing skills of the fourth grade students of SDN 007 Pulau Tinggi. The methodology of this research is classroom action research. The fourth grade students of SDN 007 became the focus of the research. Data was collected through testing many aspects of short story writing, including themes, characters, storylines, settings, messages, and storytelling techniques. The condition of students who are more focused, enthusiastic, independent, active, and cheerful is an improvement in the learning process, which helps them write better short stories. With a pre-action score of 46.49, a score of 68.10 in the first cycle, and a score of 77 in the second cycle with an increase of 31.58, the short story writing test score also increased from the first cycle to the second cycle. When using the round table learning model, students find and express ideas more easily when they make short stories. The round table learning model can be one of the models to help students develop their short story writing skills.